2016
DOI: 10.3390/ijms17101574
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25(OH) Vitamin D Levels in Polish Women during Pregnancies Complicated by Hypertensive Disorders and Gestational Diabetes

Abstract: Background: An association between the level of vitamin D and the risk of pregnancy-related complications remains unclear. The aim of this study was to examine concentrations of 25(OH) vitamin D in Polish women with normal pregnancies and pregnancies complicated by gestational hypertension, preeclampsia or gestational diabetes mellitus (GDM). Moreover, we analyzed an association between maternal serum 25(OH)D and the risk of gestational hypertension, preeclampsia and GDM. Material and Methods: The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Nevertheless, the patients were asked to estimate only the amount of time they spent outside in the summer between 10:00 a.m. and 3:00 p.m., which does not provide direct information about the exact duration of exposure to sun. Our results are consistent with the findings of other authors, who have also confirmed vitamin D deficiency among pregnant women in Poland [ 3 , 5 , 17 , 18 , 19 ], although reports in the Polish literature on better vitamin D saturation in the summer are less unambiguous. In that respect, our results are in agreement with the study by Skowrońska-Jóźwiak et al and Zasimovich et al who also confirmed season-dependent variability in vitamin D levels, with the highest values in summer and the lowest in winter [ 3 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the patients were asked to estimate only the amount of time they spent outside in the summer between 10:00 a.m. and 3:00 p.m., which does not provide direct information about the exact duration of exposure to sun. Our results are consistent with the findings of other authors, who have also confirmed vitamin D deficiency among pregnant women in Poland [ 3 , 5 , 17 , 18 , 19 ], although reports in the Polish literature on better vitamin D saturation in the summer are less unambiguous. In that respect, our results are in agreement with the study by Skowrońska-Jóźwiak et al and Zasimovich et al who also confirmed season-dependent variability in vitamin D levels, with the highest values in summer and the lowest in winter [ 3 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present sample had a high prevalence of this adverse event because the study was carried out at tertiary hospitals, where patients with a more severe diseases are referred. The association between a low vitamin D level and eclampsia/pre‐eclampsia could be attributable to the fact that vitamin D regulates the expression of vascular endothelial growth factor and pro‐inflammatory cytokines; if the vitamin D level is low, the concentration of vascular endothelial growth factor will also be low and the levels of pro‐inflammatory cytokines will be high . Levels of adiponectin have been identified as positively associated with higher levels of vitamin D in pregnancy, although the mechanism remains unclear …”
Section: Discussionmentioning
confidence: 99%
“…But 25(OH)D was not identified as a significant predictor of GDM in this study, which was consistent with this study. 7 In Mirzakhani et al, study women who had sufficient vitamin D levels (≥ 30 ng/ml) in early and late pregnancy had a significantly lower rate of preeclampsia compared with women with insufficient vitamin D levels (P = 0.04). This was not comparable to this results.…”
Section: Maternal Complicationsmentioning
confidence: 95%